Hormonal responses in heavy training and recovery periods in an elite male weightlifter - Wu, C. L.; Hung, W.; Wang, S. Y.; Chang, C. K. (Journal of Sports Science & Medicine, 2008)
We investigated the changes in serum levels of total and free testosterone and cortisol, free testosterone-to-free cortisol ratio (FTFCR), insulin-like growth factor-1 (IGF-1), and free triiodothyronine (FT3) and thyroxine (FT4) every 2 weeks for 21 weeks in an elite male weightlifter. This study was performed from August, 2003 to January, 2004, including the preparation, taper, and recovery periods for the World Championship in November, 2003. This study suggested that FTFCR may serve as a useful indicator of the degree of recovery from high-volume training commonly employed by these athletes, showing a marked decrease in high-volume training period and a significant increase after recovery. The routine measurements of these hormones would provide valuable information on physiological responses to the training program in elite athletes.